Defense against the Black Arts How Hackers Do What They Do and How to Protect against It - Varsalone, Jesse (Taylor & Francis, 2012)
As technology has developed, computer hackers have become increasingly sophisticated, mastering the ability to hack into even the most impenetrable systems. The best way to secure a system is to understand the tools hackers use and know how to circumvent them. Defense against the Black Arts: How Hackers Do What They Do and How to Protect against It provides hands-on instruction to a host of techniques used to hack into a variety of systems. Exposing hacker methodology with concrete examples, this book shows you how to outwit computer predators at their own game. Among the many things you'll learn: How to get into a Windows operating system without having the username or password Vulnerabilities associated with passwords and how to keep them out of the hands of hackers How hackers use the techniques of computer forensic examiners to wreak havoc on individuals and companies Hiding one's IP address to avoid detection Manipulating data to and from a web page or application for nefarious reasons How to find virtually anything on the internet How hackers research the targets they plan to attack How network defenders collect traffic across the wire to indentify intrusions Using Metasploit to attack weaknesses in systems that are unpatched or have poorly implemented security measures The book profiles a variety of attack tools and examines how Facebook and other sites can be used to conduct social networking attacks. It also covers techniques utilized by hackers to attack modern operating systems, such as Windows 7, Windows Vista, and Mac OS X. The author explores a number of techniques that hackers can use to exploit physical access, network access, and wireless vectors.